Analysing the socio-economic impacts of COVID-19: a new regional geography or pandemic enhanced inequalities?. Issue 1 (31st December 2022) - Cross, Katie; Evans, Jamie; MacLeavy, Julie; Manley, David
ABSTRACT: In the UK the socio-economic impacts of the COVID-19 mitigations over the course of the pandemic (March 2020 to the time of writing in January 2022) have been experienced unevenly and with differential intensities at both the regional and local scales. Using individual-level geocoded data (from the Understanding Society: UK Household Longitudinal Survey COVID-19 study) linking people to the places in which they live, we consider the regional and local disparities in the risks and outcomes of financial hardship as a result of early stage mitigations. This paper provides direct evidence from the UK of a concentration of vulnerabilities in areas of high deprivation, undermining the capacity of individuals within those areas to shelter from economic shocks. Furthermore, the geography of financial hardship appears largely compositional – attributable to the pre-existing characteristics of individuals within regions and neighbourhoods, rather than being explicitly driven by the spatial contextual effect of their social or physical environments. This has implications for UK regional economic policy, and the Levelling Up agenda in particular. It is not the regions and neighbourhoods that give rise to COVID-19 hardship per se, but the concentration of individual disadvantages of the people living within them. The persistence of compositional dis/advantages means that there is a need not only to direct ameliorative packages to the individual but also to use local areas as places where the (regional) Levelling Up agenda can break long-term place trajectories that lock in existing disparities which in turn yield unequal financial opportunities and outcomes in periods of crisis.